Narratives of Suffering in the Press: the construction of scenes and the place of the subject - Cal, Danila; Lage, Leandro (Brazilian journalism research, 2015)
The article seeks to understand the narrative strategies mobilized by press journalism to expose scenes of suffering related to child domestic labor, considered by social organizations as one of the activities in which children and adolescents are more oppressed and have their rights violated. It starts with the theoretical discussion of "politics of pity" (H. Arendt) in order to understand in journalistic narratives the suffering appropriations considering the narrative configuration of scenes and of the suffering subject. It explores ethical issues underlying these reports, questioning narrative strategies which are commonly recommended to reporters, as the thematization of injustices in the form of the complaint and a description of characters and life stories in the narratives. It concludes, in the light of the language of pity, that these stories are decisive for how child domestic labor is configured or not as a public issue and to understand the gestures of portrayal the suffering in the journalistic narratives.<!–[if gte mso 9]> <![endif]–> The article seeks to understand the narrative strategies mobilized by press journalism to expose scenes of suffering related to child domestic labor, considered by social organizations as one of the activities in which children and adolescents are more oppressed and have their rights violated. It starts with the theoretical discussion of "politics of pity" (H. Arendt) in order to understand in journalistic narratives the suffering appropriations considering the narrative configuration of scenes and of the suffering subject. It explores ethical issues underlying these reports, questioning narrative strategies which are commonly recommended to reporters, as the thematization of injustices in the form of the complaint and a description of characters and life stories in the narratives. It concludes, in the light of the language of pity, that these stories are decisive for how child domestic labor is configured or not as a public issue and to understand the gestures of portrayal the suffering in the journalistic narratives. <!–[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>